2016
DOI: 10.1089/cyber.2014.0682
|View full text |Cite
|
Sign up to set email alerts
|

Level of Immersion in Virtual Environments Impacts the Ability to Assess and Teach Social Skills in Autism Spectrum Disorder

Abstract: Virtual environments (VEs) may be useful for delivering social skills interventions to individuals with autism spectrum disorder (ASD). Immersive VEs provide opportunities for individuals with ASD to learn and practice skills in a controlled replicable setting. However, not all VEs are delivered using the same technology, and the level of immersion differs across settings. We group studies into low-, moderate-, and high-immersion categories by examining five aspects of immersion. In doing so, we draw conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 76 publications
2
93
1
1
Order By: Relevance
“…We should note that head-mounted display and virtual reality goggles may cause negative experiences such as dizziness and tiredness for some participants, as reported in [48]. Miller et al provided an excellent review on the impacts of the level of immersion in virtual reality systems on ASD treatment [49].…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…We should note that head-mounted display and virtual reality goggles may cause negative experiences such as dizziness and tiredness for some participants, as reported in [48]. Miller et al provided an excellent review on the impacts of the level of immersion in virtual reality systems on ASD treatment [49].…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…In the medical research community the concept of immersion in a task is well-received. A meta-analysis by Miller and Bugnariu (2016) showed that for high-immersion virtual environments treatment response was overwhelmingly positive for those with autism spectrum disorder who were learning social skills. Gutiérrez et al (2007) showed that students who learned how to treat a head trauma victim via a proprietary virtual HMD (they called this the “full immersion” condition) showed significantly better learning than students who learned on a laptop monitor (called “partial immersion” condition).…”
Section: Introductionmentioning
confidence: 99%
“…Non-immersive technology (low immersive), unlike semi-immersive (moderate immersive) and immersive (high immersive), is characterized by the fact that [36]:…”
Section: Definitionmentioning
confidence: 99%